Intensity Revival of Weak Symmetric Infrared Band is Possible in Ubiquinone Molecules through the Asymmetric Site-specific Isotope Labeling - Lamichhane, Hari Prasad (Himalayan Physics, 2015)
Modifications of Infrared (IR) spectral bands of ubiquinone molecule (UQ1) upon site-specific 13C labeling at the C5 or C6 position are studied in CCl4 using Gaussian 03. Polarizable continuum model (PCM) has been used to optimize the UQ1 molecule in solvent. The unlabeled neutral ubiquinone molecule consists of three intense IR bands in the frequency region between 1700 cm-1 to 1550 cm-1. The symmetric fourth band in this spectral region does not appear in the spectrum because of very weak intensity. However, site-specific 13C labeling at C5 or C6 position removes the molecular symmetry and hence there appear four equivalent IR bands in the spectral region thus considered. This observation explains why there appears an extra spectral band in the experimental spectra observed by Brudler, R. et al [1].The Himalayan Physics Year 5, Vol. 5, Kartik 2071 (Nov 2014)Page: 39-46